Creating a Draft Design and Quality Plan for Packing Material for PT. Apollo Aneka Persada Batam - Alfin Aditya Sembiring; Jani Rahardjo (Jurnal Titra, 2019)
PT. Apollo Aneka Persada (AAP) is a plastic injection company that focus on making pipe accessory (pipe and thread protector). thread protector, bevel protector, end cap, separator bar, a-rap, spacer, bumper ring, and varnish coating for pipe. International Maritime Organization (IMO) will implement a reduction from 3.5% to 0.5% sulphur for every ship, based on the new regulation that have been made in 2016. PT. There are only 2 options, whether changing the fuel or applying the scruber tank. PT. AAP has a new product for the scrubber tank and it is called Packing Material. PT. AAP still does not have any design for Packing Material and PT. AAP needs to make a design for the mold. The design was made by Solidworks in 3D model, and then converted into 2D to ease the mold maker on seeing the draft. This new product also needs to be controlled on the quality, so this research is focused on making the design of Packing Material and making a Quality Plan. This Quality Plan is to control the quality of Packing Material on every process production based on the acceptance criteria that QA Department have made.